Vinyl Freak : Love Letters to a Dying Medium - Corbett, John, 1963- (Book collections on Project MUSE., 2017)
From scouring flea markets and eBay to maxing out their credit cards, record collectors will do just about anything to score a long-sought-after album. Music writer, curator, and collector John Corbett burrows deep inside the record fiend's mind, documenting and reflecting on his decades-long love affair with vinyl. Discussing more than 200 rare and out-of-print LPs, Vinyl Freak is composed in part of Corbett's long-running Downbeat magazine column of the same name, which was devoted to records that had not appeared on CD. In other essays where he combines memoir and criticism, Corbett considers the current vinyl boom, explains why vinyl is his preferred medium, profiles collector subcultures, and recounts his adventures assembling the Alton Abraham Sun Ra Archive, an event so all-consuming that he claims it cured his record-collecting addiction. Perfect for vinyl newbies and veteran crate diggers alike, "Vinyl Freak" plumbs the motivations that drive Corbett and collectors everywhere